National treasure 2 book of secrets - Turteltaub, Jon; Bruckheimer, Jerry (California : Walt Disney Pictures, 2008)
Benjamin Franklin Gates is looking for a book containing centuries of secrets and must take several actions to recover it, including kidnapping the President of the United States
Title from title screen
Bonus features: audio commentary with director Jon Turteltaub and actor Jon Voight
Director of photography, Amir Mokri, John Schwartzman ; editors, William Goldenberg, David Rennie ; music, Trevor Rabin ; costume designer, Judianna Makovsky ; production designer, Dominic Watkins ; visual effects supervisor, Mitchell S. Drain, Christopher James Hall
Cast: Nicolas Cage, Jon Voight, Justin Bartha, Diane Kruger, Helen Mirren, Ed Harris
DVD Format
Dolby digital
Keywords: Treasure troves -- Drama; Lost articles -- Drama